Efektivitas ekstrak umbi sarang semut (myrmecodia pendens merr.& perry) sebagai penurun kadar glukosa darah tikus sprague dawley yang diabetes mellitus - Raya, Maxianus Kopong; Legowo, Anang M.; Wijayahadi, Noor (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background : Diabetes Mellitus (DM) is a disease associated with pancreatic Î² cell damage and causes hyperglycemia Antioxidants were effective in reducing the state of hyperglycemia that was triggered by free radicals. Sarang semut contains flavonoids and tannins that act as antioxidants.Objective : The purpose to analyze the effectiveness of sarang semut stem extract as lowering blood glucose on diabetic white male Sprague Dawley rats. Method : True experimental with 30 rats which divided into five groups : negative control (DM+ water), positive control (DM+glibenklamid) and 3 treatment groups of DM + water extract ofÂ sarang semut stem powder 90 mg/200gBW, 180 mg/200g BW and 360/200g BW respectively. DM was induced by 65mg/kgBW Streptozotocin and 230 mg/kgBW Nicotinamide intraperitonealy. Extract was given by sonde. The data was analyzed by Kruskall-Wallis and Mann-Whitney. Results : IC50 value of Â sarang semut stem extract were 6,56-10,07 mg/ml in powder and 9,12-15,62 mg/ml whole. The average rats weight alteration on groups of negative control, positive control,Â and 3 treatment groups of DM + water extract ofÂ sarang semut stem powder 90 mg/200gBW, 180 mg/200g BW and 360/200g BW before and after treatment were -7,60Â± -0,40; 25,80Â±0,51; 16,40Â±0,44; 17,20Â±1,28 dan 19,20Â±0,06 gram respectively (Ï=0,001). The average fasting blood glucose level on groups of negative control, positive control,Â and 3 treatment groups of DM + water extract ofÂ sarang semut stem powder 90 mg/200gBW, 180 mg/200g BW and 360/200g BW before and after treatment were 3,33Â±2,42; -122,44Â±-0,51; -79,42Â±-11,38; -94,08Â±-11,97 and -134,66Â±-2,59 mg/dL respectively (Ï=0,001). Conclusion : The IC50Â value in sarang semut stem powder was higher than a whole form. Dose of 360 mg/200g BW lowered blood glucose better than 90 and 180 /200g BW dosage.